The Effects of the Fear of Missing Out on People's Social Networking Sites Use During the COVID-19 Pandemic: The Mediating Role of Online Relational Closeness and Individuals' Online Communication Attitude - Gioia, Francesca; Fioravanti, Giulia; Casale, Silvia; Boursier, Valentina (Frontiers in Psychiatry, 2021)
Forced isolation induced by COVID-19 pandemic dramatically impacted individuals’ well-being, reducing the opportunities for social encounters, consequently resulting in a greater use of social media in order to maintain social relationships. Although the range of friend-related activities appeared to be severely constrained during quarantine, the Fear of Missing Out (FoMO) needs to be carefully examined, especially in relation to problematic social networking site use (PSNSU). Indeed, FoMO might enhance individuals’ need to stay connected and communicate with other people, leading to PSNSU, in order to face the fear of being invisible in the world of social media in circumstances of physical isolation. The present study sought to evaluate the predictive role of FoMO on PSNSU during the COVID-19 pandemic, testing the mediating effect of online relational closeness and online communication attitude. A total of 487 Italian adults (59.3% women), aged between 18 and 70 years (mean age = 29.85 years; SD = 9.76), responded to an online survey during the period of COVID-19 pandemic lockdown in Italy. The survey included self-report measures assessing perceived FoMO, online communication attitude, relational closeness with online friends, and PSNSU. Participants declared they spent significantly more time social networking during the pandemic, particularly women. The total model accounted for a significant amount of variance in participants’ PSNSU (R2 = .54; F(9,447) = 58.285, p <. 001). Despite the other people's social rewarding experiences had been drastically reduced by the lockdown, findings showed a direct effect of FoMO on PSNSU. Moreover, FoMO had an effect on online communication attitude and online relational closeness, although only online communication attitude predicted, in turn, PSNSU. Conversely, relational closeness on social networking sites did not predict PSNSU. The present study suggests that, during COVID-19 lockdown, FoMO levels may have strengthened attitudes toward online communication, which, in turn, may have put some individuals at risk of PSNSU.